Development of Hybrid Aluminium Air Battery-Fuel Cell System - Khor, Zheng Yu (2020)
Due to the constant increase in electric demand of our society, new energy production, transport and storage systems will play a key role in a near future. Regarding to energy storage systems, electrochemical energy storage is a potential candidate because of direct conversion from chemical energy to electrical energy and vice versa. Aluminium is a very promising energy carrier given its high capacity and energy density, low cost, earth abundance and environmental benignity. Traditional aluminium air battery experiences impediment from the self-corrosion and related safety problems. In this study, a new approach was proposed to ameliorate the issue and developed to study the performance of the cell; by incorporating an additional hydrogen-air fuel cell into the system. The hybrid system turned the self-corrosion issue into a beneficial reaction by utilizing the hydrogen gas produced from aluminium for fuel cell. 2-electrode and 3-electrode configuration were employed using LSV technique to obtain cell polarization curve. The hybrid cell displayed significant improvement after integrating the fuel cell, the open circuit voltage was 1.3 V and power output increases by 44 % from 6.20 mW – 8.93 mW. From the polarization curve, the cell was limited by overpotential loss such as ohmic loss, activation loss and mass transport loss. Optimization was carried out to augment the performance of the hybrid cell. The hydrogen anode and cathode air were changed to graphite felt, besides, increasing the dimension of air cathode to increase intake of ambient air. The optimized cell recorded an additional increase of 10.67 mW compare to carbon cloth-based cathode. Aluminium utilization test was conducted with different concentration of electrolyte and utilization efficiency is able to reach up to 90.2 %. The maximum-power density of the-entire hybrid-system increases-significantly by-over 20% after incorporating-the hydrogen-air sub cell; the-increase was-even significant-with higher-concentration of-electrolyte. The-hybrid system is-adaptable in concentrated-alkaline electrolyte with-significantly-improved-power output at no-sacrifice of its-overall efficiency. Discharge cell efficiency was tested at 10 mA, 20 mA and 50 mA the discharge efficiency of the hybrid cell range from 75.4 % - 91.7 %.”